2013
DOI: 10.1016/j.crci.2013.01.013
|View full text |Cite
|
Sign up to set email alerts
|

New aspects of gold nanorod formation via seed-mediated method

Abstract: Gold nanorods (AuNRs) were obtained via a wet chemistry technique, in aqueous medium, employing crystallisation seeds. The kinetics of formation, the aspect ratio, and the selectivity of the particles were evaluated according to the parameters of synthesis: the growth-driving agent, seed, and gold precursor concentrations. In 2-4 h, the rod particles attained the expected size and shape under kinetic control, and were stable for at least 2 days. In order to obtain good quality AuNRs in good yields, without enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 72 publications
(77 reference statements)
0
5
0
1
Order By: Relevance
“…No observed when GNRs were kept in the mother solution with native CTAB concentration. Recently, analogous spectrophotometric changes following the synthesis have been reported by da Silva [42]. Interestingly, the authors observed such variations when CTAB was not removed from the GNRs'solution.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…No observed when GNRs were kept in the mother solution with native CTAB concentration. Recently, analogous spectrophotometric changes following the synthesis have been reported by da Silva [42]. Interestingly, the authors observed such variations when CTAB was not removed from the GNRs'solution.…”
mentioning
confidence: 65%
“…[22] The lack of a molecular level understanding of the fabrication mechanism leads to major difficulties in controlling the reproducibility and poses questions on the interplay of different variables determining the shape and the AR. Moreover, the occurrence of aging phenomena [23] still needs adequate characterization, and further compromises the fine control of the size and the structure of GNRs. Secondly, GNRs obtained by seed-mediated growth are capped by a double layer of cetyl trimethyl ammonium bromide (CTAB), a surfactant that plays a critical role in driving the seeds' growth towards the cylindrical shape.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, in the seed-mediated synthesis of AuNRs, the growth of these anisotropic nanoparticles is mediated by the addition of metallic gold atoms at the surface of previously prepared small gold nanoparticles (seeds), by a controlled reduction of Au­(I) species at the surface of the seeds that grow in an anisotropic way due to the presence of cetyltrimethylammonium bromide (CTAB) as a growth-driving agent. ,, Indeed, many studies of these standard synthesis methods and adaptations thereof have appeared in the literature. In particular, the effects of the seed size, cosurfactants, additives, temperature, , surfactant chain length, and headgroup structure have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Vale também comentar que agentes de modificação de superfície podem apresentar uma maior afinidade por um tipo de faceta cristalina da nanopartícula que outra. Essa propriedade é importante tanto para a geração de nanopartículas anisotrópicas, 40 quanto para realizar automontagens com orientações especificas das nanopartículas, gerando, consequentemente, arranjos nanoestruturados singulares. 99 Devido à promoção de interações químicas específicas e seletivas, muitos conectores são à base de biomoléculas (proteínas, peptídeos, filamentos da cadeia do DNA etc.).…”
Section: Funcionalização De Superfície De Nanopartículas Com Moléculaunclassified